ANALISIS NILAI TAMBAH KELAPA MENJADI KOPRA DI DESA PEMATANG KAMBAT KECAMATAN SERUYAN HILIR TIMUR KABUPATEN SERUYAN (STUDI KASUS INDUSTRI KOPRA UDIN) - Siti Rizka Noviyanti; Tri Yuliana Eka Sintha; Masliani, Masliani (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2018)
The research objectives are: 1) Knowing the processing of coconut into copra in the copra udin industry, 2) Analyzing the large value added by the copra udin industry owner. This research was carried out in the copra udin industry in the village of Pematang Kambat, Seruyan Hilir Timur District, Seruyan Regency. This industry is the largest copra industry when viewed from the number of workers and its production capacity of 6.42 kw/week compared to other industries in the village of Pematang Kambat. The types of data used in this study include primary data and secondary data. Primary data is data obtained from the results of research by interviewing directly with the owner of the industry assisted by a list of questions. Secondary data is data obtained from various sources such as textbooks, journals, and related institutions. The research method used is a case study and data analysis used is qualitative and quantitative descriptive analysis. This study used a qualitative descriptive analysis to explain the process of processing coconut into copra in the Udin Kopra Industry which is still traditional in nature which consists of several stages starting from the supply of raw materials in the form of coconut, coconut husk stripping, coconut cleavage, drying stage 1, plucking, drying stage 2, chopping and packaging which still uses a lot of human power compared to the engine. Quantitative analysis was used to analyze the value of coconut added to the Udin Copra Industry which was assisted by the Hayami Method. The added value of coconut processing into copra is IDR 1,119.60 which is the difference from the copra per kilogram value with a ratio of added value of 50.89%, and obtains a margin of IDR 1,200.00 which is distributed to each factor of production, namely: 1) . Labor benefits are 75% which is the highest production factor where the factor ratio is > 40%; 2). The contribution of other inputs is 6.70% which is the lowest production factor where the production factor ratio is <15%; while 3). The company's profit of 18.30% is a medium production factor where the factor production ratio is between 15-40%.